Avaliação preliminar da tipologia de tratamento de água para o Rio Jundiaí baseado em dados históricos de qualidade - Araújo, Larissa Silva; Mânica, Alana Natalí; Fonseca, Camila Gomes Marchesini; Isaac, Ricardo de Lima (International Workshop for Innovation in Safe Drinking Water, 2022)
The raw water quality is the determining factor for a drinking water treatment plant technology selection. In this context, the purpose of this work was to present the most indicated water treatment type for surface water from the Jundiaí River, collected in Salto City (São Paulo State, Brazil), based on secondary historical data of water quality and technical-scientific literature. The range of historical monitoring data suggests that the assessed water resource is located in an environmentally unprotected and polluted watershed, suggesting that conventional treatment is the most appropriate for drinking water purposes, with potential optimizations even by operational improvements or the application of pre-treatment and/or advanced treatment steps. Nonetheless, treatability studies should be carried out to assist the water treatment technology selection, considering both technical, economic, and non-economic aspects.